2022
DOI: 10.3389/fpsyg.2022.829193
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship Amongst University Student Perceived Learning Burnout, Academic Self-Efficacy, and Teacher Emotional Support in China’s English Online Learning Context

Abstract: This study seeks to explore the impact of learning burnout on university students’ English learning effect in the online environment. Through a large sample questionnaire survey, the study uses structural equation modelling to measure the interactions amongst university students’ English online learning burnout (EOLB), academic self-efficacy (AEE), and teacher emotional support (TES), thereby analysing and summarising the characteristics of their impacts on students’ online learning satisfaction. The results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Analysis of causal relationships of sub-factors highlights inappropriate of the home for study and learning, the stress and concern of being infected with the coronavirus, and heavy family and work responsibilities (net effect) lead to an imbalance between work, life and study, and the difficulty of adapting the home environment to online learning (net effect). Impact of fear of infection with the coronavirus on student burn out has been reported in 21 study. This finding is consistent with the findings of 29 that the inadequacy of the home environment in online education is a problem that leads to student stress.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Analysis of causal relationships of sub-factors highlights inappropriate of the home for study and learning, the stress and concern of being infected with the coronavirus, and heavy family and work responsibilities (net effect) lead to an imbalance between work, life and study, and the difficulty of adapting the home environment to online learning (net effect). Impact of fear of infection with the coronavirus on student burn out has been reported in 21 study. This finding is consistent with the findings of 29 that the inadequacy of the home environment in online education is a problem that leads to student stress.…”
Section: Discussionmentioning
confidence: 95%
“…The high level of prevalence and severity of academic burnout among online students during the Covid-19 pandemic has been reported by numerous studies 13 , 18 21 . Pavlakis and Kaitelidou (2012) showed that distance learning can lead to problems such as depression, stress and burnout 22 .…”
Section: Introductionmentioning
confidence: 82%
“…for Chinese college students. The research that has already been done includes Charkhabi, Azizi Abarghuei, and Hayati (2013); Lee, Jeon, Lee, and Jeon (2015); Rohmani and Andriani (2021) and Yang, Sun, and Jiang (2022) Lee, & Podsakoff, 2003). I study so badly that I really want to give up.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, universities are increasingly relying on digital formats for learning as part of their training and further education. Many studies showed that online learning is available at a large number of universities, but these can vary considerably depending on the type, sponsorship, and size of the universities [53,54]. In recent years, online learning has been developed, tested, and used many times at universities of applied sciences [55].…”
Section: Online Learning At Universities Of Applied Sciencesmentioning
confidence: 99%